How accurate are leukocyte indices and C-reactive protein for diagnosis of neonatal sepsis? - da Silva, Orlando (Pulsus Group Inc, 1998)
Early diagnosis of neonatal sepsis is often difficult to make. Treatment on the basis of clinical suspicion and risk factors may result in overtreatment. A previous review of the usefulness of C-reactive protein and leukocyte indices concluded that these test results should be interpreted with caution. The present paper reviews and, when appropriate, revises, in light of new information, the conclusions reached in the previous systematic review of the topic.